INVESTING IN PRESCHOOL AGE CHILDREN – A CASE STUDY OF VIDZEME REGION (LATVIA) - Rajevska, Feliciana; Reima, Katrine (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Social investments are important for a child’s development and future success. Parental leaves and Early Childhood Education and Care services (ECEC) are among main forms of social investment, contributing to child poverty reduction and increasing equality, as well as underpinning the potential for skilled workers in the future. The aim of the paper is to analyse availability of the main forms of social investment in preschool age children - early childhood education services and parental leaves, in Vidzeme region (Latvia) for a case study. An analysis of policy documents, parents’ surveys at pre-school institutions, interviews with education institution representatives and local authorities regarding education and social matters were conducted in the research. The support system for parents is still dominated by the “passive” form of support system. However, social investment policies are becoming increasingly more important. This is achieved by supporting parents' access to social investment services and by increasing the amount of parental leave benefits. In 2013-2015 funding for child-care and family policy has increased. Expenditure growth was mostly affected by an increase in the allowance for childcare and the minimum parental allowance. The availability of ECEC is moderate, but since 2009 private institutions and since 2013 babysitting services have been co-funded at the national level till May 31, 2016 to improve it. Since September 2015 a 3-year innovative project “Vouchers for the provision of child minder services to workers with nonstandard work schedules” has been introduced too, to promote parental employment and work and family balance. In Vidzeme region, for example, service availability is additionally stimulated by free transport services, ECEC fee discounts for poor, low-income and large families, etc. Results show that the availability of ECEC has been improved and there has been signs of positive changes in children’s development. Nevertheless, the availability of ECEC is moderate, and in some poorer municipalities in Latvia Matthew effects can be spotted – the middle and highest strata of society use services to a higher extend then the low-income society.